Czym jest dziś czytanie literatury? (ankieta) - Abramowska, Janina (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2013)
In response to the questionnaire, Professor Janina Abramowska chooses the Bible, and the poetry of Jan Kochanowski and Wislawa Szymborska as the most important books. She also talks about her passion for journalism and crime stories, as well as the works of Amos Oz as a perfect read on a gray and gloomy day.